Influence of Sintering Temperature on Crystal Phase, Microstructure and Surface Resistivity: Pr0.75Na0.25Mn0.98Cr0.02O3 - Elly Shahira Mat Sidik; T. W. Lin; A. Azizi; Suhadir Shamsuddin (Enhanced Knowledge in Sciences and Technology, 2024)
This study investigates the impact of varying sintering temperatures (1100 °C, 1150 °C, and 1200 °C) on the crystal phase, microstructure, and surface resistivity of Pr0.75Na0.25Mn0.98Cr0.02O3, a monovalent perovskite manganite. Employing a solid-state reaction method, samples underwent meticulous preparation and characterization using Powder X-ray Diffraction (XRD), Scanning Electron Microscopy (SEM) with Energy Dispersive X-ray Analysis (EDX), and a four-point probe for surface resistivity. XRD analysis reveals an orthorhombic structure with the Pnma group, demonstrating changes in lattice parameters as sintering temperature increases. SEM imaging highlights irregular grain shapes, with heightened densification at higher temperatures. Furthermore, EDX measurements confirm the accurate composition of all samples, devoid of impurity peaks. The precise determination of the elemental composition percentages included Pr, Na, Mn, Cr, and O.